Poverty-inequality and economic crisis: past, present and future. A critical analysis - Peña-Vinces, Jesús C. (Universidad de San Buenaventura - Cali, 2017)
This article from diverse points of view (economic, politic and religious) make a critic analysis of the past, present, and future of poverty and inequality. This manuscript mainly focuses on the respond of three question few discussed by the academic community: Why are the poor, poor? What will happen to the poor in 2050?. Will there be any solution?. Furthermore, the paper is useful for any person with a low level of specialization, since it has been carried out with a language very simple and with a little orientation in Latin America.